Effects of the cranial parasite Tylodelphys sp. on the behavior and physiology of puye Galaxias maculatus (Jenyns, 1842) - López-Rodríguez, Ruby; George-Nascimento, Mario; Górski, Konrad (PeerJ, 2021)
Diplostomatid digeneans are well-known manipulators of the behavior of their intermediate hosts. Unencysted metacercariae of Tylodelphys sp. inhabit the cranial cavity of the fish Galaxias maculatus; however, to date they have not been documented to alter their host behavior. The goal of this study was to evaluate the potential effects of Tylodelphys sp. inhabiting the cranial cavity of Galaxias maculatus on host physiology and swimming behavior as well as its reaction to a simulated predation attempt. Blind experiments in the lab were carried out on 56 fish that were filmed individually. The Fulton condition factor (K) was used as an approximation of nutritional status and a respirometry chamber was used to evaluate oxygen consumption rates of fish. Of the 56 fish, 21 were parasitized by Tylodelphys sp. (mean intensity = 30, range from 1 to 101). Parasitized and non-parasitized fish were similar in condition factor and oxygen consumption rates. Furthermore, the oxygen consumption rate of G. maculatus was not correlated with the abundance of Tylodelphys sp. However, parasitized fish more frequently swam close to the water surface, whereas non-parasitized fish more frequently swam at intermediate depths. When faced with a simulated predator attack, unparasitized fish showed more frequent fleeing behavior as well as a more intense post-fleeing activity. Collectively, these results suggest that Tylodelphys sp. inhabiting the cranial cavity of fish may alter their behavior predisposing them to predation by birds.
Keywords: Cranial cavity; Intermediate host; Diplostomatid larvae; Manipulation; Unencysted metacercariae